1984
DOI: 10.1515/znc-1984-3-418
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Aglycones in the Leaf Resin of Some Cistus Species

Abstract: Members of the genus Cistus excrete a leaf resin that consists mainly of terpenoids. This resin also contains methylated flavonoids as aglycones. Rare methyl derivatives of myricetin have been isolated from C. monspeliensis, along with uncommon methyl derivatives of quercetin. Further flavonoids encountered in the leaf resin of this and six further species are methyl derivatives of kaempferol and quercetin, some of apigenin and in one species also of luteolin. The results indicate that there might exist specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A tea prepared from the leaves is used as hypoglycaemic and the flowers and buds decoction is used for the treatment of peptic ulcers in Turkish folk medicine (Sezik et al, 1991;Yesilada et al, 1995). In previous phytochemical studies, Cistus laurifolius have been reported to contain flavonoids including quercetin, kaempferol, apigenin, luteolin and theirs methyl-ethers, the coumarine scopoletin, diterpenoids, sesquiterpenoids, and sugars (Demetzos et al, 1989;Vogt et al, 1987;Wollenweber and Mann, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…A tea prepared from the leaves is used as hypoglycaemic and the flowers and buds decoction is used for the treatment of peptic ulcers in Turkish folk medicine (Sezik et al, 1991;Yesilada et al, 1995). In previous phytochemical studies, Cistus laurifolius have been reported to contain flavonoids including quercetin, kaempferol, apigenin, luteolin and theirs methyl-ethers, the coumarine scopoletin, diterpenoids, sesquiterpenoids, and sugars (Demetzos et al, 1989;Vogt et al, 1987;Wollenweber and Mann, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Myricetin 3,4',5',7-tetramethyl ether 1 ( Figure 1) was first isolated several years ago from leaves of C. monspeliensis and later from other plants and its structure was assigned on the basis of UV-vis, IR and 1 H-NMR spectroscopy [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Another important compound found in high proportions in C. ladanifer extracts is the carotenoid derivative norisoprene called 2,2,6-trimethylcyclohexanone (Gomes et al 2005;Greche et al 2009;Mariotti et al 1997;Oller-López et al 2005;Ramalho et al 1999;Robles et al 2003;Santos et al 2017;Teixeira et al 2007;Verdeguer et al 2012;Weyerstahl et al 1998;Zidane et al 2013), which is one Barros et al (2013); Chaves et al (1997aChaves et al ( , b, 1998Chaves et al ( , 2001); Fernández-Arroyo et al 2010; Guimarães et al (2009); Gomes et al (2005); Greche et al (2009); Gulz (1984); Mariotti et al (1997);Oller-López et al (2005); Pascual et al (1982); Proksch and Gulz (1980a, b); Ramalho et al (1999); Rincón et al (2000); Robles et al (2003); Santos et al (2017); Sosa et al (2004); Teixeira et al (2007); Verdeguer et al (2012); Vieira et al (2017); Vogt et al (1987); Weyerstahl et al (1998); Wollenweber and Mann (1984) Extracts (Gomes et al 2005;Greche et al 2009;Gulz 1984;Mariotti et al 1997;…”
Section: Odoriferous Compoundsmentioning
confidence: 99%
“…It is traditionally obtained by boiling the plant material in water (Dias et al 2005). However, other solvents have been applied either to plant material or resin, for analytical purposes of labdanum constituents: chloroform (Alías et al 2012;Chaves et al 1997aChaves et al , 1998Vogt et al 1987), ethanol (Chaves et al 1993), acetone (Wollenweber and Mann 1984), hexane (Pascual et al 1982) and with water followed by organic solvents such as dichloromethane (Ramalho et al 1999) and ethanol (Greche et al 2009). Extraction with water has the advantage (over organic solvents) of being more ecologic and environmentally friendly (Barrajón-Catalán et al 2011).…”
Section: Chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation